Перспективи використання методів просторовочасового доступу в системах мобільного зв'язку - Столяренко, О. А. (ХНУРЕ, 2021)
As the number of mobile users in the world and in Ukraine is rapidly increasing, at the same time the signal-interference situation is complicated, the conditions of radio wave propagation in the used frequency bands are deteriorating, so the use of adaptive antenna solutions is necessary to increase the physical radio resource high-speed services
Keywords: SDМА; мобільний зв'язок